The predictive and prognostic value of CA 125 in endometrial cancer - Darja Arko; Tanja Tašner; Iztok Takač (Acta Medico-Biotechnica, 2021)
Endometrial cancer is the most common malignant tumour of the female genital tract. It affects mainly older women, with postmenopausal bleeding as the primary symptom. The diagnosis of endometrial cancer is confirmed by histological evaluation of tissue specimens and described as either type I or type II. Treatment includes surgery (hysterectomy, adnexectomy and dissection of pelvic and paraaortic lymph nodes), radiotherapy, chemotherapy and hormonal therapy. Preoperative serum CA 125 (Cancer Antigen 125 or Carbohydrate Antigen 125) concentrations are correlated with depth of myometrial invasion, lymph node metastases, positive peritoneal cytology and invasion of the lymphovascular space, and can assist in making decisions about the extent of surgery. Preoperative CA 125 levels have prognostic value; postoperative levels serve as a predictor of early recurrence. Elevated serum CA 125 is linked not only with endometrial cancer, but also with several benign and malignant conditions, including ovarian cancer. Other tumour markers (e.g., CA 15–3, CA 19–9) and a promising new marker human epididymis protein 4 (HE4) can also be used for managing patients with endometrial cancer.